Micro-station sleeping algorithm based on coverage area priority in 5G network - Ziren WANG; Yi LI (Dianxin kexue)
With the maturity of 5G mobile communication technology and the rapid growth of the number of mobile terminals, the problem of intensive energy consumption of 5G wireless communication system base stations is prominent.A micro base station area hierarchical sleep algorithm was proposed.Considering the impact of micro base station load, inter station distance and inter layer cooperation on micro base station sleep, the transitions number of the micro base station in the overlapping coverage area between macro base stations is less, and the priority sleep operation has a good energy-saving effect.The simulation result shows that the energy-saving rate is 23%, which can adapt to different network sizes, and the energy-saving effect is better in large-scale networks.